Are Local Milieus the Key to Innovation Performance? - Dirk Czarnitzki; Hanna L. Binz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This study investigates how local milieus foster innovation success of firms. We complement the common practice of linking firm performance indicators to regional characteristics with survey evidence on the perceived importance of locational factors. While the former approach assumes that location characteristics affect all firms in the same way, the survey allows us to model firms judging the attractiveness of locations by a heterogeneous set of criteria. It turns out that the availability of highly skilled labor and the proximity to suppliers matters for firms? innovation performance. Interestingly, location factors obtained from the survey provide a more accurate explanation on how local milieus facilitate innovation.
More recent version: http://hdl.handle.net/10419/27575
Keywords: O31; O38; 330; Innovation performance; R&D; location factors; Flanders; Innovation; Unternehmensentwicklung; Region; Standortfaktor; Forschungskooperation; Flandern